To instill fear or love: Terrorist groups and the strategy of building reputation. (July 2018) - Akcinaroglu, Seden; Tokdemir, Efe
Why does one terrorist group employ actions that win the hearts and minds of its constituency while another resorts to tactics that alienate their support? The paper investigates terrorist groups' strategy of building reputation in their constituency/in-group population and non-constituency/out-group population. Studying all domestic terrorist groups between 1980 and 2011 with original data, we find that ethnic/religious groups and those with territorial control invest in positive reputation in their constituency as they can minimize the risks of returns. Radical groups and those with cross-border support, however, tend to build negative constituency reputation. While the former type of group has a small constituency, the latter ones can find resources across borders, which reduces their dependency on the constituency. Lastly, we find that terror groups seeking policy concessions avoid building a negative reputation in their non-constituency as this strategy enhances their chances of negotiating with the government.